SEDIMENT TRANSPORT IN RILL FLOW UNDER DEPOSITION AND DETACHMENT CONDITIONS - Polyakov V.O.; Nearing M.A. (My University, 2003)
The understanding of soil erosion processes and the development of accurate erosion prediction models require understanding of detachment, deposition, and sediment transport in rills. The objectives of this study were to determine whether sediment transport capacity is a unique value for given soil, flow rate, and slope, and to determine if equilibrium sediment concentration in the rill obtained by detachment was different from that observed under depositional conditions. Experiments on a Carmi loam (fine, mixed, mesic Typic Hapludalf) simulated rill erosion under net detachment and net deposition conditions. Two discharge rates of 6 and 9 l min−1 and two sediment input regimes of 0 and excess of transport capacity were tested on soil beds with lengths of 2, 4, 6, 7, and 8 m at 7% slope. Sediment load reached steady state conditions within the 8-m distance on the rill. At 9 l min−1 discharge, 8 m length, and excess sediment added to the flow, sediment delivery was 71 g l−1 versus 31 g l−1 for the corresponding case with no sediment added. Overall, for the conditions tested, rill flow transported two times more sediment than it could detach. The flow did not reach its maximum potential transported load through detachment of soil due in part to changes in the sediment size distribution under deposition and possibly to the protective action of bedload particles moving along the rill bottom and/or changes in flow turbulence associated with sediment laden flow.
Keywords: Erosion; Rill erosion; Runoff; Sediment; Sediment transport; Soil erosion